PHYTOCHEMICAL ANALYSIS OF LEAVES OF TECTONA GRANDIS LINN. - ASHVIN G. GODGHATE; RAJARAM S. SAWANT (International Journal of Pharma and Bio Sciences, 2014)
Tectona grandis Linn belongs to the family Verbenaceae. The plants Tectona grandis Linn Commonly known as ‘Teak’ is a large to very large deciduous tree, 20-35 m in height with light brown bark. Present study deals with the phytochemical properties which have been carried out on the leaves of Tectona grandis Linn using Acetone, Chloroform, Methanol and Water solvents. Out of four solvents, Chloroform extract contains more number of secondary metabolites whereas Methanolic extract contain least number of secondary metabolites.